2023
DOI: 10.1038/s41598-023-40991-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene expression profiling for accurate endometrial receptivity testing

Alvin Meltsov,
Merli Saare,
Hindrek Teder
et al.

Abstract: Expressional profiling of the endometrium enables the personalised timing of the window of implantation (WOI). This study presents and evaluates a novel analytical pipeline based on a TAC-seq (Targeted Allele Counting by sequencing) method for endometrial dating. The expressional profiles were clustered, and differential expression analysis was performed on the model development group, using 63 endometrial biopsies spanning over proliferative (PE, n = 18), early-secretory (ESE, n = 18), mid-secretory (MSE, n =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…69 A previous study that also used the beREADY model to determine receptivity profiles of endometrium samples, detected a significantly higher proportion of displaced WOI in the RIF group than in the fertile group. 43 The results of our study, however, do not indicate a displacement of the WOI in the RIF group compared with the fertile group (ie our long-term analysis). A potential explanation for this difference could be that the endometrium samples in our study were taken prospectively.…”
Section: Ta B L Econtrasting
confidence: 65%
See 1 more Smart Citation
“…69 A previous study that also used the beREADY model to determine receptivity profiles of endometrium samples, detected a significantly higher proportion of displaced WOI in the RIF group than in the fertile group. 43 The results of our study, however, do not indicate a displacement of the WOI in the RIF group compared with the fertile group (ie our long-term analysis). A potential explanation for this difference could be that the endometrium samples in our study were taken prospectively.…”
Section: Ta B L Econtrasting
confidence: 65%
“…Individual receptivity profiles of endometrial biopsies were analyzed with the beREADY receptivity dating model. 43 Simulating the original targeted RNA‐seq method, 68 biomarkers with four housekeeping genes were selected from the quantified whole‐genome sequencing data. 44 This filtered gene set was then further analyzed with the beREADY model.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The beREADY test, which assesses endometrial receptivity based on receptivity-related gene expression, 16 , 17 was performed on all 29 RIF patients. 14 The endometrial RNA was extracted with a Qiagen miRNeasy Mini kit and sequenced and analyzed in CCHT.…”
Section: Methodsmentioning
confidence: 99%
“…So far, no proof exists to support such an assumption, and hence analyses performed in one cycle might not guarantee the correct identification of the WOI in the next cycle. Alternatives to the ERA test have been suggested [ 211 , 212 , 213 , 214 ]. Indeed, high throughput RT-qPCR has been applied to compare the expression of 184 genes involved in endometrial receptivity and immunity in endometrial biopsies from fertile and sub-fertile patients.…”
Section: Transcriptomic Signature and Secretome Analysismentioning
confidence: 99%
“…Using a similar approach, He et al developed an RNA-Seq-based endometrial receptivity test (rsERT) to identify the WOI in RIF patients, and reported a significant increase in implanted embryos, intrauterine pregnancy, and live birth rate in patients undergoing rsERT-guided pET, compared to patients undergoing conventional ET [ 213 ]. More recently, a new test based on Targeted Allele Counting by sequencing (TAC-seq) and named beREADY has been proposed for endometrial dating [ 214 ]. The analysis of 68 endometrial receptivity genes in endometrial biopsies of healthy volunteers allowed the researchers to identify pre-receptive (proliferative and early secretory samples), receptive (mid-secretory samples), and post-receptive (late secretory samples) stages of the endometrium, thus contributing to the identification of WOI displacement in RIF patients and when to proceed to a personalized embryo transfer.…”
Section: Transcriptomic Signature and Secretome Analysismentioning
confidence: 99%